2011
DOI: 10.1378/chest.11-0221
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Community-Acquired Respiratory Distress Syndrome Toxin-Producing Mycoplasma pneumoniae in Refractory Asthma

Abstract: A sthma is a prevalent and heterogeneous disease that not only has a marked effect on the quality of life of affected patients but also imparts a signifi cant economic burden on society. The term "refractory asthma" (RA) is used for patients with persistent asthma symptoms in whom comorbidities have been treated, triggers addressed, compliance with treatment evaluated, and alternative diagnoses excluded. 1 The link between bacterial processes and RA has emerged as various phenotypes of chronic asthma with pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
54
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 24 publications
5
54
0
Order By: Relevance
“…However, what is becoming clearer is the link between M. pneumoniae infection, CARDS toxin activity, and asthma (6,8,10,11,15,17,22,23). Recently, we reported a case series where we detected the prolonged presence (up to18 mo) of CARDS toxin protein in the respiratory secretions of a subset of patients with refractory asthma (41). These data are in good agreement with the current literature where emerging experimental and clinical data strongly links M. pneumoniae and M. pneumoniae-associated virulence factors to wheezing and exacerbation asthma (19, 21-25, 39, 42, 43).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, what is becoming clearer is the link between M. pneumoniae infection, CARDS toxin activity, and asthma (6,8,10,11,15,17,22,23). Recently, we reported a case series where we detected the prolonged presence (up to18 mo) of CARDS toxin protein in the respiratory secretions of a subset of patients with refractory asthma (41). These data are in good agreement with the current literature where emerging experimental and clinical data strongly links M. pneumoniae and M. pneumoniae-associated virulence factors to wheezing and exacerbation asthma (19, 21-25, 39, 42, 43).…”
Section: Discussionmentioning
confidence: 97%
“…The ability of rCARDS toxin to promote allergic inflammation may have a profound impact on the exacerbation of human asthma. A direct role for CARDS toxin in human asthma has not been proven, but it would not be unreasonable to predict a role for CARDS toxin in human lung disease (41,45).…”
Section: Discussionmentioning
confidence: 99%
“…, 2008, Waites & Talkington, 2004). Evidence linking the organism to reactive airway diseases, such as asthma, is rapidly accumulating (Esposito et al , 2000, Kraft, 2000, Biscardi et al , 2004, Nisar et al , 2007, Sutherland & Martin, 2007, Peters et al. , 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For example, we reported that M. pneumoniae was detected in 52% of the respiratory secretions from a cohort of refractory asthmatics. Among the M. pneumoniae -positive refractory asthmatic patients, all tested positive for CARDS toxin by antigen capture indicating the presence of the toxin in the airway and suggesting an important role of CARDS toxin in asthmatic lung disease [14]. Additionally, Wood et al showed a strong correlation between poor asthma control and testing positive for CARDS toxin by antigen capture suggesting that M. pneumoniae infection and CARDS toxin can worsen asthma symptom severity and control [15].…”
Section: Introductionmentioning
confidence: 99%